The Effect of Gingival Inflammation on Salivary Cytochrome P450 Enzymes in Children: A Case-Control Study - Radhi, Nada; Yassin, Heba N; Diab , Ban (Scripta Medica, 2026)
Background/Aim: Gingival inflammation in children involves characteristic changes of the salivary composition that reflect not only weakened local defence factors but also increased defensive reflexes. This study aimed to compare the salivary parameters cytochrome concentration, density and flow rate between children with gingival inflammation and clinically healthy gingiva. Methods: A total of 86 children were included and divided into two groups: 41 with gingival inflammation and 45 with healthy gingiva, which was gender matched for age. Unstimulated saliva was collected and cytochrome concentration, salivary density and flow rate were measured. Results: Participants with gingival inflammation had significantly lower mean salivary cytochrome concentration and density but showed increased salivary flow rate compared to healthy controls. These differences were found in both sexes, being more marked in boys with respect to the age increase of flow rate. Correlation studies showed a strong negative correlation between salivary density and flow rate in both groups. These results indicate that there is a unique biochemical signature for gingival inflammation in children, which includes lower cytochrome and density, accompanied by an increase in flow rate.Conclusion: In children, gingival inflammation was associated with reduced salivary CYP450 and density and increased flow rate in saliva, suggesting a unique biochemistry of oral disease.
Keywords: Gingivitis; Cytochrome p-450 enzyme system; Child; Case-control studies; Clinical enzyme tests; Oral health; Paediatrics